Implementation of Students Rules on Punishment In Islamic Perspective - Sulaiman Sulaiman (Al-Hayat Al-Istiqomah Foundation, 2019)
This research caused by the ineffectiveness of the implementation of student discipline on the punishment. The research aims to reveal, 1) the implementation of student rules regarding punishment in the Islamic perspective, 2) the effectiveness of the implementation of student rules regarding punishment in the Islamic perspective, 3) the obstacles in implementing student discipline regarding punishment in the Islamic perspective. This research used descriptive methods and qualitative approaches. The research conducted at Mujahidin Private Senior High School. The subject of this study was the counselling teacher and the teacher of Islamic education. Data collection techniques used are observation, interviews, and documentation. The data analysis technique used data reduction, data display, and conclusion. The validity checking data technique used in this study is data triangulation. The results of the research: 1) Implementation of the rules has been applied to the maximum, considering students have understood the prevailing rules and regulations as well as students who violate but are still said to be reasonable because they are only related to minor violations. 2) There is an awareness of his mistakes and the responsibility to improve them. The decline in the number of violations is also evidence of the increase in awareness in carrying out school discipline and the progress made by this school because of implementation punishment. 3) The inhibiting factor is the student itself related to awareness, environment, and parents. While the supporting factor is the cooperation that exists between the school and students.Penelitian ini disebabkan oleh ketidakefektifan penerapan disiplin siswa pada hukuman. Penelitian ini bertujuan untuk mengungkapkan, 1) implementasi aturan siswa tentang hukuman dalam perspektif Islam, 2) efektivitas penerapan aturan siswa tentang hukuman dalam perspektif Islam, 3) hambatan dalam menerapkan disiplin siswa mengenai hukuman dalam Islam perspektif. Penelitian ini menggunakan metode deskriptif dan pendekatan kualitatif. Penelitian dilakukan di SMA Swasta Mujahidin. Subjek penelitian ini adalah guru konseling dan guru pendidikan Islam. Teknik pengumpulan data yang digunakan adalah observasi, wawancara, dan dokumentasi. Teknik analisis data menggunakan reduksi data, tampilan data, dan penarikan kesimpulan. Teknik pemeriksaan data validitas yang digunakan dalam penelitian ini adalah triangulasi data. Hasil penelitian: 1) Implementasi aturan telah diterapkan secara maksimal, mengingat siswa telah memahami aturan dan peraturan yang berlaku serta siswa yang melanggar tetapi masih dikatakan wajar karena hanya terkait dengan pelanggaran kecil. 2) Ada kesadaran akan kesalahannya dan tanggung jawab untuk memperbaikinya. Menurunnya jumlah pelanggaran juga merupakan bukti meningkatnya kesadaran dalam melaksanakan disiplin sekolah dan kemajuan yang dibuat oleh sekolah ini karena hukuman pelaksanaan. 3) Faktor penghambatnya adalah siswa itu sendiri terkait dengan kesadaran, lingkungan, dan orang tua. Sedangkan faktor pendukungnya adalah kerja sama yang ada antara sekolah dan siswa.